2012
DOI: 10.1103/physrevb.85.140504
|View full text |Cite
|
Sign up to set email alerts
|

Coherent superconducting quantum pump

Abstract: We demonstrate nonadiabatic charge pumping utilizing a sequence of coherent oscillations between a superconducting island and two reservoirs. The pumping rate for each elementary cycle is limited by the coupling between the island and the reservoirs given by the Josephson energy. Our experimental and theoretical studies show that relaxation can be employed to reset the pump in order to avoid accumulation of errors due to nonideal control pulses. Thus our results demonstrate the effects of nonadiabatic quantum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The suggested SI would release the equality Mð 12 CÞ ¼ 0:012 kg=mol, which has raised criticism. In particular, there have been claims that the definition of the kilogram based on h would not be understandable for the wider audience, and a definition based on the mass of a number of elementary particles would be better in this respect (Becker et al, 2007;Milton, Williams, and Bennett, 2007;Leonard, 2010;Hill, Miller, and Censullo, 2011). Milton, Williams, and Forbes (2010) studied two alternatives, fixing either N A and h or N A and the atomic mass constant m u ¼ M u =N A , and showed that this choice has little effect on the uncertainties of fundamental constants, mainly because the ratio h=m u is well known from atomic recoil experiments.…”
Section: The Future Simentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested SI would release the equality Mð 12 CÞ ¼ 0:012 kg=mol, which has raised criticism. In particular, there have been claims that the definition of the kilogram based on h would not be understandable for the wider audience, and a definition based on the mass of a number of elementary particles would be better in this respect (Becker et al, 2007;Milton, Williams, and Bennett, 2007;Leonard, 2010;Hill, Miller, and Censullo, 2011). Milton, Williams, and Forbes (2010) studied two alternatives, fixing either N A and h or N A and the atomic mass constant m u ¼ M u =N A , and showed that this choice has little effect on the uncertainties of fundamental constants, mainly because the ratio h=m u is well known from atomic recoil experiments.…”
Section: The Future Simentioning
confidence: 99%
“…( 21). Although the system dynamics employed for such Cooper-pair pumping can be of different kindssee, e.g., (Hoehne et al, 2012), the most typical is the adiabatic dynamics (Geerligs et al, 1991), in which the pumped charge is related (Aunola and Toppari, 2003;Möttönen et al, 2008;Pekola et al, 1999) phase or (Faoro et al, 2003) its non-abelian extensions.…”
Section: Coulomb Blockade Of Cooper Pair Tunnelingmentioning
confidence: 99%
“…They could be used as building blocks for quantum computing devices, 7 or to create a quantized current source that would pair up with the Josephson voltage and quantum Hall resistance to close the so-called quantum metrology triangle. 8 Among different types of realizations, Cooper-pair pumps [9][10][11][12] stand out as macroscopically coherent objects, with the phase of the superconducting order parameter in the leads playing a key role. In addition, the cyclic path is described in the space of parameters when pumping is equipped with a nontrivial geometric structure, allowing for the observation of geometric-phase effects.…”
mentioning
confidence: 99%
“…A Cooper-pair pump 1 is a superconducting device that can be used to transport Cooper pairs by manipulating some of its parameters in a periodic fashion. Cooper-pair pumps have recently attracted considerable theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimental [17][18][19][20][21][22] attention.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of Cooper-pair pumps have been proposed and realized 17,18,21 . All these devices comprise the same building blocks, namely, superconducting islands connected to each other and to superconducting leads by Josephson junctions.…”
Section: Introductionmentioning
confidence: 99%